Egypt-Searching for Binding Constraints on Growth - Enders, Klaus-Stefan (IMF Working Papers; Working Paper ;, 2007)
Since 2004 Egypt's growth has been accelerating in step with the launching of a series of ambitious reforms, reversing a trend during the preceding half-decade when Egypt's growth rate fell below that of most regional peers and well below that of the average developing country. This paper seeks to identify factors that held back Egypt's growth in the recent past, and explores whether recent reforms have removed the most binding constraints to allow at least a temporary growth spurt. Overall, the Egyptian reforms launched in 2004 appear to have focused well on the most critical constraints-reducing red tape and tax rates, and improving access to foreign exchange-thereby getting a strong growth response out of a limited set of reforms. However, inefficient bureaucracy remains an important obstacle to higher growth and reforms in this area should continue to have high payoffs. Ongoing reforms are also addressing constraints that are likely to become binding soon (or have become so already), such as inefficient financial intermediation and high public debt. Improvements in education may rapidly become a critical factor for sustaining higher growth.